NADP-Dependent Malic Enzyme 1 Participates in the Abscisic Acid Response in Arabidopsis thaliana - Arias, Cintia L.; Pavlovic, Tatiana; Torcolese, Giuliana; Badia, Mariana B.; Gismondi, Mauro; Maurino, Verónica G.; Andreo, Carlos S.; Drincovich, María F.; Gerrard Wheeler, Mariel C.; Saigo, Mariana (Frontiers in Plant Science, 2018)
Arabidopsis thaliana possesses three cytosolic (NADP-ME1-3) and one plastidic (NADP-ME4) NADP-dependent malic enzymes. NADP-ME2 and -ME4 show constitutive expression, in contrast to NADP-ME1 and -ME3, which are restricted to particular tissues. Here, we show that NADP-ME1 transcript and protein were almost undetectable during normal vegetative growth, but gradually increased and reached levels higher than those of the other isoforms in the latest stages of seed development. Accordingly, in knockout nadp-me1 mature seeds the total NADP-ME activity was significantly lower than in wild type mature seeds. The phenotypic analysis of nadp-me1 plants indicated alterations of seed viability and germination. Besides, the treatment with abscisic acid (ABA), NaCl and mannitol specifically induced the accumulation of NADP-ME1 in seedlings. In line with this, nadp-me1 plants show a weaker response of primary and lateral root length and stomatal opening to the presence of ABA. The results suggest that NADP-ME1 plays a specialized role, linked to ABA signalling during the seed development as well as in the response to water deficit stress.